A pilot study comparing the pharmacokinetics of injectable cyanocobalamin and hydroxocobalamin associated with a trace mineral injection in cattle. Issue 3 (8th March 2021) - Gonzalez‐Rivas, Paula A.; Chambers, Michael; Liu, Jerry
Abstract: Injectable vitamin B12 (cobalamin) is traditionally used to prevent or treat vitamin B12 deficiencies in ruminants. Sheep and human studies have demonstrated the superiority of a single dose of hydroxocobalamin (OHB12) over cyanocobalamin (CNB12) in maintaining high levels of cobalamin in plasma and liver. However, limited data are available for cattle. The purpose of this study was to compare the pharmacokinetics of two forms of cobalamin—OHB12 and CNB12—as a single subcutaneous injection of 28 µg/kg BW at the same time of a trace mineral injection in six non‐cobalt/B12 ‐deficient Holstein‐Friesian steers. Plasma and liver samples were obtained to determine cobalamin concentration after treatment. Cyanocobalamin had lower retention in plasma and liver than OHB12 (p < .05). Cobalamin levels peaked in plasma by 8 h after treatment in both groups. However, OHB12 reached a higher peak compared to CNB12. Levels of cobalamin in plasma dropped closer to baseline levels 24 h after CNB12 treatment while OHB12 maintained higher concentrations. Hydroxocobalamin increased significantly hepatic concentration of cobalamin 28 days after treatment, while CNB12 did not increase liver levels relative to pre‐treatment (p < .05). These results confirm that a single subcutaneous OHB12 injection increases the level of cobalamin in the blood in the first 24 hours, and this increase is maintained in the liver for at least 28 days.